Integrated circuit engineering establishing a foundation - Herbst, L.J (Textbooks in electrical and electronic engineering, 1996)
This text gives a comprehensive coverage of integrated circuits. In three parts, the first deals with processing, component formation and device modelling. The second part covers digital and analogue circuits, including semiconductor memories, with performance summaries of commercial products. The final part explains the nature of application specific integrated circuits (ASICs) and the ASIC design process. The final chapter covers VLSI scaling and the dominant role of interconnections in the scaling process. The text caters for engineers and scientists who need to have a grasp of IC capabilities and ASIC design rooted in an appreciation of processing, device, behaviour, and circuit practice. It should also be of interest to undergraduate electronic engineering students or others studying computer engineering and physics or taking courses on microelectronics.